Total Abdominal Hysterectomy Versus Total Laparoscopic Hysterectomy. A Hospital Based Study - Ruksana Farooq; Azhar un Nisa Quraishi; Sheema Posh (Dr. Annil Mahajan, 2023)
Background: Hysterectomy is one of the most surgical procedures performed. It can be performed by abdominal, vaginal or laparoscopic route. Laparoscopic Hysterectomy is reported to have low postoperative morbidity, less blood loss, shorter hospital stays and early return to normal activities. The main limitation to laparoscopic approach is medical or anesthetic disorders that don't allow adequate pneumoperitoneum or proper ventilation. Aims and Objectives: This study was conducted to compare intra and postoperative results of Total Abdominal Hysterectomy and Total Laparoscopic Hysterectomy. Study Design: It was a prospective cohort study. Materials and Methods: Total abdominal and Total Laparoscopic hysterectomies, with or without bilateral salphingoopherectomy performed for the treatment of benign gynecological disease were included in the study. Results: A total of 65 patients were taken in each group. There was no significant statistical difference between the two groups with respect to intraoperative complications. Out of postoperative complications, wound infection [p=0.013], Resuturing [p=0.028], ileus [ p=0.038], hemoglobin drop [p<0.001] and postoperative blood transfusion [p=0.032], were found more in TAH group with significant p value of less than 0.05. Also, the duration of surgery [p<0.001], time of ambulation since surgery [p<0.001] and mean days of hospital stay [p<0.001] was found more in TAH group than TLH group, with significant p value of less than 0.05. Conclusion: TLH offers many advantages over TAH.